Navigating Economic Uncertainty: Exploring The Impact Of Reduced Bank Credit On The Construction Industry - Faizul Mubarok; Arie Wibowo Khurniawan; Irmawaty (Jurnal Reviu Akuntansi dan Keuangan, 2023)
Purpose: This paper aims to analyze credit in the Indonesian banking construction sector empirically. Specifically, we examine whether economic conditions affect construction sector credit and how the response and diversity of construction sector credit in the face of economic shocks. Methodology/approach: This article use monthly data on Indonesian banking credit from 2004 to 2022 using the Vector Error Correction Model (VECM). Findings: The long-term effects of the economy on credit are shown by the results of the VECM research. The Impulse Response Function (IRF) results indicate that credit in the construction industry has both positive and negative effects. Forecast Error Variance Decomposition (FEVD) analysis shows that gross domestic product, crises, industrial price index, interest rates, exchange rates, and inflation affect credit diversity. Practical implications: Banking credit is an essential component in meeting company needs. Banks need to consider several things in the distribution of credit to the construction sector, especially those that impact the long term. Originality/value: This research provides a better understanding of how the construction sector credit can be affected by changing economic conditions, and how diverse credit responses and policies are in the face of such shocks.